The Effects of Tantalum Additive on the Crystal Structure, Microstructure and Transformation Temperatures of TiNb-based ?-Ti Alloys - Ercan, Ercan; Dağdelen, Fethi (Bitlis Eren Üniversitesi, 2020)
?-type Ti-based alloys are materials which widely used in the aerospace industry and medical fields because it has a sufficient biocompatibility and high temperature resistance. Reinforcement with low-density, high corrosion resistance and non-toxic elements, such as Nb and Ta alloying with ?-type of Ti-based alloys even more attractive. X-ray, microstructure, and transformation temperatures of TiNb(24,5-x)Ta(x = 0,1,2,3,4) (at. %) alloys were investigated. The DSC analysis showed only ??? reverse transformation for the temperature range of 5,5 oC to 41,1 oC. DSC results were found to be compatible with X-ray analysis taken at room temperature. It was found that ? phases were in small amounts despite dominant ? phases. The dominance of the ? phase has shown that the Ta and Nb elements are a good ? stabilizer. It was determined from the optical microscope images that the ? phase, grains, and grain boundaries in alloys increased with the addition of Ta. From SEM-EDX results, it was found that ? phase is a precipitation. Additionally, the EDX results showed that Ta elements concentration increased in the grain boundaries. Valance electron concentration (ev?a) and concentration of valance electron (cv ) values indicated that the alloy with low values of (ev?a

?-tipi Ti-esaslı alaşımlar yüksek sıcaklıktaki dayanıklılığı ve biyo-uyumluluğu sayesinde uzay sanayisi ve medikal alanlarda kullanımı yaygın olan materyallerdir. Nb ve Ta gibi düşük yoğunluklu, üstün korozyon direnci ve toksik olmayan özelliklere sahip elementler ile takviye edilmesi, ?-tipi Ti-esaslı alaşımları daha da çekici hale getirmiştir. TiNb(24,5-x)Ta(x=0,1,2,3,4) (at. %) oranlarında hazırlanan alaşımların X-ışını, mikroyapı ve dönüşüm sıcaklıkları incelendi. DSC analizlerinden 5,5 oC to 41,1 oC aralığında sadece ??? ters dönüşümü gözlenmiştir. Oda sıcaklığında yapılan XRD analizleri ile DSC sonuçlarının uyumlu olduğu görülmüştür. Baskın ? fazlarına karşın ? fazlarının küçük miktarlar da olduğu tespit edilmiştir. ? fazının baskın olması Ta ve Nb elementlerinin iyi bir ? stabilizatörü olduğunu göstermiştir. Optik mikroskop görüntülerinden alaşımlardaki ? fazı, taneler ve tane sınırlarının artan Ta ilavesiyle belirginleşmiştir. SEM-EDX görüntülerinden ? fazının çökelti olduğu görülmüştür. Ayrıca EDX sonuçları ile Ta element konsatrasyonunun tane sınırlarında arttığı bulunmuştur. Alaşımların (ev?a) ve (cv ) oranları oda sıcaklığı altında dönüşüm sergileyen düşük değerli (ev?a
TiNb-esaslı ?-Ti Alaşımlarının Kristal Yapı, Mikroyapı ve Dönüşüm Sıcaklıklarına Tantal Katkısının Etkileri
Keywords: Engineering; Mühendislik